Design and test of 2ZLX-2 transplanting machine for oil peony - Ji, Jiangtao; Cheng, Qun; Jin, Xin; Zhang, Zhihong; Xie, Xiaolin; Li, Mingyong (International Journal of Agricultural and Biological Engineering, 2020)
In order to improve the quality of oil peony transplanting, based on the characteristics of peony seedlings and the transplanting effect, the transplanting process was analyzed. A peony seedling transplanting machine was designed, which was mainly composed of a chain-clamp type planting mechanism (clamp, transmission chain, sprocket), slideway, profiling wheels, trencher, the power transmission system and rack. Through the movement analysis of the planting mechanism and its operation process, its structural parameters were optimized. The effective length of the clamp was determined as L1=235 mm, the adjustment range was 235-285 mm, and the height of the planting trajectory was H=340 mm. Based on the physical characteristics and mechanical characteristics of the peony seedlings, the parameters of the slideway and the putter were determined. The effective length of the slideway was determined as L2=420 cm, the width T2=105 mm, the distance between the slideways S=45 mm. The initial angle difference of the putter was θ=13°, and the putter rotation angle β=37°, putter height ratio ε=2. Based on the above parameters and design requirements, the radius of the planting sprocket R1=42 mm, R2=80 mm. “Feng Dan” peony seedlings were used as transplantation test objects. The results showed that: when the planting frequency was 60-75 plants/min, the upright rate was 89.2%-92.8%, the leakage rate was 0-0.28%, the injury rate of seedlings was 0, and the qualified rate of planting depth was 91.7%-95.3%, the variation coefficient of plant spacing was 0.25%-0.54%. This machine can effectively improve the quality and efficiency of transplanting, meeting the requirements of mechanical design and production needs. Keywords: peony transplanting, planting mechanism, oil peony, peony seedlings, parameter design, test analysis DOI: 10.25165/j.ijabe.20201304.5695 Citation: Ji J T, Cheng Q, Jin X, Zhang Z H, Xie X L, Li M Y. Design and test of 2ZLX-2 transplanting machine for oil peony. Int J Agric & Biol Eng, 2020; 13(4): 61–69.